Simulation of AC-DC Converter for High Power Application - Ramarajan Sundaramoorthy; R.Samuel Rajesh Babu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This manuscript deals with the simulation of AC - DC Zeta converter for high power drive application with greater efficiency, lesser losses and power factor correction. It involves simpler control circuitry with less external components. The explanation of Fundamental function of Zeta converter is given in this paper. To condense the harmonic content the PI, PID and Fuzzy Logic controller are used. The operation of Zeta converter in open loop, closed loop is obtained. Closed loop system of zeta converter proves better performance over open loop system. Open and closed loop circuits are simulated by using MATLAB simulink. By giving disturbance in closed loop and open loop systems, feat of Zeta converter is compared.